Meningkatkan Kualitas Hidup Lansia melalui Skrining Index Massa Tubuh di Tlogomas Malang - Achmad Masfi; Eri Yanuar Akhmad Budi Sunaryo; Yhenti Widjayanti; Nurul Evi; Muhammad Putra Ramadhan; Qory Tifani Rahmatika; Nurma Afiani; Ronal Surya Aditya (Jurnal Pemberdayaan Umat, 2023)
Purpose: The well-being of the elderly can be reflected in their health condition, both physically, spiritually, and socially which enables everyone to live productively socially and economically. Modern lifestyles have changed human attitudes and behavior, including diet, smoking, consumption of alcohol, and drugs as a way of life so that people with degenerative diseases (diseases caused by decreased organ function) are increasing and life-threatening. The purpose of this community service is in the form of screening for Body Mass Index in the elderly. Methodology: The method used is measurement and examination as well as providing education. Methods for measuring Body Mass Index and conducting counseling about healthy lifestyles for the elderly in Tlogomas village. Results: The results of the screening conducted, of the 55 participants who took part in the examination, found 19 people had frequent activities, 11 people had problems related to physical activity with rarely doing activities, and 15 people had problems very rarely doing activities. Conclusions: This Community Service Program runs smoothly and can provide benefits to the community. The results of this Community Service Program can be used as a reference for improving the health status of the elderly. Limitations: The area for community service is limited to the Tlogomas area. Contribution: This research is useful for the elderly in improving a healthy lifestyle in the gerontological area.